Soft Law Strategy in the ASEAN Charter Framework - Didi Jubaidi; Dyah Ersita Yustanti (China Quarterly of International Strategic Studies, 2025)
This research examines the role of soft law strategies within the framework of the ASEAN Charter to enhance regional cooperation. Soft law, which refers to nonlegally binding agreements, principles, and declarations, is an important instrument in directing the behavior of ASEAN member states and shaping regional norms. This research aims to explore the effectiveness of soft law in achieving the goals outlined in the ASEAN Charter, focusing on the areas of economic cooperation, environmental protection, and human rights. The authors employ a qualitative research methodology, utilizing both primary and secondary sources. Primary data are obtained from official ASEAN documents, while secondary data come from academic literature and related reports. Soft law in the ASEAN Charter is found to play a significant role in promoting dialog and cooperation among member states. However, its effectiveness is often limited by the lack of enforcement mechanisms and varied commitments among members. While soft law has great potential in strengthening regional integration, further efforts are needed to improve implementation and adherence to agreed-upon principles.